2011
DOI: 10.1007/s11262-011-0591-y
|View full text |Cite
|
Sign up to set email alerts
|

Infectivity analysis of a blackgram isolate of Mungbean yellow mosaic virus and genetic assortment with MYMIV in selective hosts

Abstract: Yellow mosaic disease in grain legumes in Indian subcontinent is caused by two important virus species viz. Mungbean yellow mosaic virus (MYMV) and Mungbean yellow mosaic India virus (MYMIV), belonging to the genus Begomovirus of the family Geminiviridae. The genomic components of a begomovirus causing yellow mosaic disease in blackgram in southern India were cloned and sequenced. Nucleotide sequence comparison of DNA A component shows the virus isolate to be a variant of Mungbean yellow mosaic virus:-(MYMV-[I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…YMD caused by Begomoviruses (family Geminiviridae, genus Begomovirus) has emerged as the major threat. This disease currently is a major hazard to the flourishing production of mungbean in India, Sri Lanka, Pakistan, Bangladesh, Papua New Guinea, Philippines, and Thailand [6][7][8][9]. YMD was first reported in lima bean (Phaseolus lunatus) in 1940 [10] and was subsequently discovered in other plants, such as Dolichos bean (Dolichos lablab) [11,12] and mungbean [13].…”
Section: Introductionmentioning
confidence: 99%
“…YMD caused by Begomoviruses (family Geminiviridae, genus Begomovirus) has emerged as the major threat. This disease currently is a major hazard to the flourishing production of mungbean in India, Sri Lanka, Pakistan, Bangladesh, Papua New Guinea, Philippines, and Thailand [6][7][8][9]. YMD was first reported in lima bean (Phaseolus lunatus) in 1940 [10] and was subsequently discovered in other plants, such as Dolichos bean (Dolichos lablab) [11,12] and mungbean [13].…”
Section: Introductionmentioning
confidence: 99%
“…Of these MYMIV and MYMV are most important as these infect large number of legumes in India. MYMIV is more predominant in northern, central and eastern regions of India (Usharani et al 2004) and MYMV in southern region (Karthikeyan et al 2004;Girish and Usha 2005;Haq et al 2011) to which Tamil Nadu state belongs.…”
Section: Introductionmentioning
confidence: 99%
“…Correlation between whitefly population and disease incidence showed positive non-significant relation with each other in all the locations. The regression analysis revealed that, per cent contribution of weather factors on whitefly population and disease incidence at Kavalur, Raichur (Haq et al, 2011).…”
Section: Issn: 2319-7706 Volume 6 Number 10 (2017) Pp 94-104mentioning
confidence: 98%